2020
DOI: 10.1155/2020/6943860
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabonomic Study Reveals Intervention Effects of Polydatin on Potassium Oxonate-Induced Hyperuricemia in Rats

Abstract: Previous studies have disclosed the antihyperuricemic effect of polydatin, a natural precursor of resveratrol; however, the mechanisms of action still remain elusive. The present study was undertaken to evaluate the therapeutic effects and the underlying mechanisms of polydatin on potassium oxonate-induced hyperuricemia in rats through metabonomic technology from a holistic view. Nuclear magnetic resonance (NMR) spectroscopy was applied to capture the metabolic changes in sera and urine collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
(68 reference statements)
3
15
0
Order By: Relevance
“…Polydatin (PD, C 20 H 22 O 8 ) is a natural active ingredient extracted from the dried roots of the perennial herb Polygonum cuspidatum Sieb. et Zucc., which might play a potential therapeutic role in various kidney disorders, such as AKI [7][8][9][10][11][12][13][14][15][16], diabetic nephropathy [17][18][19][20][21][22][23][24], lupus nephritis [25], and hyperuricemia [26][27][28], and has been used to treat patients with irritable bowel syndrome in Europe [29]; moreover, PD has been shown to exhibit mechanisms to antioxidant stress, anti-inflammation, and antifibrosis characteristics; improvement of mitochondrial damage; and regulation of autophagy [9,30,31]. Resveratrol, an aglycone of PD, has been verified to ameliorate myocardial and liver damage caused by iron overload [32][33][34]; moreover, it has been confirmed that resveratrol can reduce iron load in hemodialysis patients in clinical studies [35].…”
Section: Introductionmentioning
confidence: 99%
“…Polydatin (PD, C 20 H 22 O 8 ) is a natural active ingredient extracted from the dried roots of the perennial herb Polygonum cuspidatum Sieb. et Zucc., which might play a potential therapeutic role in various kidney disorders, such as AKI [7][8][9][10][11][12][13][14][15][16], diabetic nephropathy [17][18][19][20][21][22][23][24], lupus nephritis [25], and hyperuricemia [26][27][28], and has been used to treat patients with irritable bowel syndrome in Europe [29]; moreover, PD has been shown to exhibit mechanisms to antioxidant stress, anti-inflammation, and antifibrosis characteristics; improvement of mitochondrial damage; and regulation of autophagy [9,30,31]. Resveratrol, an aglycone of PD, has been verified to ameliorate myocardial and liver damage caused by iron overload [32][33][34]; moreover, it has been confirmed that resveratrol can reduce iron load in hemodialysis patients in clinical studies [35].…”
Section: Introductionmentioning
confidence: 99%
“… 61 Here, we demonstrate the renal safety of carvacrol that was not previously observed with other natural compounds, such as polydatin, which decreases the serum uric acid level but increases the serum creatinine level, thereby indicating abnormal metabolic status in hyperuricemic rats. 62 In addition, carvacrol exhibited a relative safety profile because no impairment was observed in the kidneys. The serum creatinine and urea levels were also normal and similar to previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the reduction of Bacteroides and Bifidobacteria found in the HUA rat model can be subsequently restored by supplementing with tuna oligopeptides (TMOP). Furthermore, after transplanting the fecal microbiota of TMOP-treated mice, the phenotypes of hyperuricemia and renal inflammation were attenuated, indicating that the beneficial effects of TMOP on HUA are at least partially mediated by intestinal microbes ( 163 ). In addition, prebiotics can also reduce chronic inflammation in the host by regulating the intestinal microbiota, thereby alleviating hyperuricemia.…”
Section: Manuscript Formattingmentioning
confidence: 99%